Maqasid al-Shari’ah in Islamic Law Renewal: The Impact of New Normal Rules on Islamic Law Practices during the Covid-19 Pandemic (Mazahib, 2021)
The vast and multidimensional impact of the Covid-19 pandemic has forced all countries to establish policies to prevent the transmission of Covid-19, including Indonesia. Not a few countries are not ready to make decisions to find new, more effective ways to prevent Covid-19. In Islamic law, ijtihad is part of lawmaking in the implementation of worship and muamalah, which solves problems that arise and mitigates policy implementation. This article uses a normative juridical approach to the issue because it can showcase the benefit of Islamic law for humans. Moreover, it aims to generate ideas in the renewal of Islamic law, especially in the implementation of worship and muamalah (social transaction/relation), and inform the government to make decisions that intersect with Islamic law during the Covid-19 pandemic. The focus of this research is how does covid-19 affect the practice of Islamic law in worship and mu`amalah? This study finds that government policies and regulations are currently in line with Islamic law. The most critical considerations in determining the compatibility of government policies and rules with shari’a are maintaining the soul’s safety, maintaining the continuity of religion through rukhshah, and maintaining the economy. Also, the Islamic rulings (fatwa) issued by ulama in response to government policies and rules are expected to guide worship and mu`amalah, build awareness and solidarity of Muslims, and relate to the people’s economy today.